Advances in Nematology - Christoforou, Michalakis (My University, 2026)
Michalakis Christoforou was awarded the prize for the best Student Oral Presentation for his paper on "Identification and Mapping of Potato Cyst Nematodes in Cyprus using Molecular Tools and Geographical Information Systems", at Advances in Nematology. at the Linnean Society, London
Keywords: Sciences